Trastorno del espectro autista y desarrollo cognitivo en niños en la primera infancia, de la unidad educativa “Pio Jaramillo Alvarado” periodo 2023-2024 - Poma Cartuche, Carmen del Rocío (2024)
The present curricular integration work entitled: Autism spectrum disorder and cognitive development in children in early childhood, from “Pio Jaramillo Alvarado” educational unit, period 2023-2024; it was carried out with the purpose of analyzing the cognitive development in children in early childhood with Autism Spectrum Disorder, it was a qualitative, descriptive study, non-experimental design, and cross-sectional. An observation and interview guide were applied as techniques to collect information, to the teaching sample. The results obtained through these instruments indicate that it is necessary to strengthen teacher training in the area of ASD and at the same time promote collaboration between the school, the family and experts, since it is essential to provide comprehensive support adapted to the needs. individual of each child, since they need personalized attention. Which allows us to understand the particular characteristics of this population and implement appropriate educational strategies. Based on the results, a structured methodological strategy guide of five activities was implemented for teachers with the purpose of strengthening knowledge and guaranteeing comprehensive care that responds to the individual needs of each child with autism spectrum disorder. It is concluded that after the application of the strategy guide, the teacher's interest in acquiring knowledge about how to work with children with ASD was evident and her participation was active throughout the process whose purpose was to guarantee comprehensive and quality care. with an individualized approach in the educational care of this population. This demonstrates that methodological strategies promote cognitive development and at the same time contribute significantly to the progress and well-being of students during their learning process.